COP26's dilemma: sustainability vs food security? - Montesclaros, Jose Ma. Luis P. (2022)
Ironically, amidst the push to “phase down” coal reliance, the world is seeing a “coal crunch” of rising coal/energy prices, with serious implications on fertilisers and food. Countries pursuing sustainability initiatives ignore these trade-offs at their own peril.